Physico-chemical properties of premixes for preparation of "akara" (2004)
Premix was formulated from cowpea flour, peper powder and onion powder by mixing the ingredients together this was then packed. Proximate chemical composition and fucntional properties (water absorption capacity, solubility index, foaming capacity and foam stability) of the cowpea flour as affected by inclusion of other ingredients were determined. Inclusion of other ingredients separately and jointly in cowpea flour had siginificant effects on functional properties but little effect on proximate chemical compositions of cowpea flour. Foaming and water absorption capacities were decreased as a result of added ingredients. Akara prepared from pre-formulated premix prior to re-hydration into paste compared favourably with the control akara from freshly prepared cowpea paste but had texture rated lower and low overall acceptability